2006
DOI: 10.1017/s0265021506000913
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for prilocaine-induced methaemoglobinaemia following peripheral regional anaesthesia

Abstract: The use of prilocaine for regional block is safe, since the older patients who might be more susceptible to suffer from clinical symptoms of methaemoglobinaemia usually form less methaemoglobin. However, since prediction of high methaemoglobin levels is difficult, anaesthesiologists performing regional blocks in patients who might be jeopardized by a decreased oxygen transport capacity should avoid high doses of prilocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 19 publications
0
30
0
7
Order By: Relevance
“…In a study, the EMLA cream was found to be more effective compared to a bonain mixture for eardrum anesthesia (14). However, it was found that prilocaine has a high propensity to cause methemoglobinemia (15)(16)(17). Thus, it became important to search for more compounds that could form a eutectic mixture with lidocaine and thereby, improve its effectiveness (18).…”
Section: Introductionmentioning
confidence: 99%
“…In a study, the EMLA cream was found to be more effective compared to a bonain mixture for eardrum anesthesia (14). However, it was found that prilocaine has a high propensity to cause methemoglobinemia (15)(16)(17). Thus, it became important to search for more compounds that could form a eutectic mixture with lidocaine and thereby, improve its effectiveness (18).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated doses were not necessary. Mean recovery time was 10.2±3.5 [4][5][6][7][8][9][10][11][12][13][14][15][16] hours. The plasma G6PD levels were normal in all neonates.…”
Section: Resultsmentioning
confidence: 99%
“…Prilocaine is widely used in children and adults as a local anesthetic agent, and its metabolite o-toluidine can cause methemoglobinemia. The dose of prilocaine and the age of the infant are the most important predictive factors for higher MetHb formation [7]. Infants are more vulnerable to methemoglobinemia because they have higher gastric pH than that in older children, and this causes greater bacterial proliferation of the intestinal flora that can convert the ingested nitrate to nitrite [6].…”
Section: Mutlu Et Al Acquired Methemoglobinemia In Infantsmentioning
confidence: 99%
“…However, there has been little research conducted on methemoglobin formation associated with the administration of injectable local anesthetics for dental treatment. [13][14][15] Based on the widespread use of local anesthetics in dentistry and their ability to potentially cause methemoglobinemia, dental practitioners need more information on the disorder and its toxic manifestations. It is particularly important that dental clinicians treating pediatric dental patients use dosing guidelines that preclude clinical toxicity.…”
mentioning
confidence: 99%
“…5,8,[13][14][15] In the human body, prilocaine is metabolized into o-toluidine and nitrosotoluidine, both of which are responsible for the oxidation of hemoglobin to methemoglobin. 4 According to a retrospective study by Guay,5 prilocaine was associated with 68 out of 242 (28%) of the literature's documented episodes of acquired methemoglobinemia.…”
mentioning
confidence: 99%